FUNGSI PENGAWASAN INTERNAL OLEH APARAT PENGAWASAN INTERN PEMERINTAH (APIP) PADA PEMERINTAH DAERAH KABUPATEN BUTON SELATAN - Muhamad Gazali; La Ode Islamy Hisanuddin; Rasmuin (Governance, 2024)
This research aims to describe and analyze the supervisory function Government Internal Oversight Apparatus (APIP) in preventing budget misuse in the South Buton Regency Regional Government. The theory used is the theory expressed by Winardi, namely the concept of supervisory formulation which consists of establishing standards or bases for supervision, examining the results achieved, comparing implementation with standards, determining differences if there are differences, and correcting deviations with corrective actions. This research uses a qualitative descriptive approach with data collection techniques through interviews, observations and document studies, which are then analyzed using interactive techniques from Miles and Huberman which consist of data collection, data reduction, data presentation and conclusion drawing. The Government's Internal Supervision Apparatus (APIP) in preventing budget abuse in the South Buton Regency Regional Government can operate by carrying out quality assurance activities including audits (financial audits, performance audits and audits for specific purposes), evaluation, monitoring, socialization of supervision, education/training, guidance, and consultancy as well as communication of supervision results through supervision results reports. This function is carried out in Financial audits carried out at 15 risk-based SKPDs, performance audits at the fisheries service, probity audits at 5 strategic packages, BOS fund management audits at education units, and village financial management audits and the most effective review activities are carried out as a preventive measure such as review of budget activity plans, review of self-estimated prices, and expenditure budget plans.